x ; y ; z are three numbers that satisfy:
⎩ ⎪ ⎨ ⎪ ⎧ x 2 + y 2 + 2 ( x y + y z + z x ) = 1 1 9 y 2 + z 2 + 2 ( x y + y z + z x ) = 1 2 8 z 2 + x 2 + 2 ( x y + y z + z x ) = 1 3 5
Calculate ∣ x y z ∣ .
This is part of the series: " It's easy, believe me! "
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
If we label the equations 1, 2, and 3 from top to bottom, then
2-1: z 2 − x 2 = 9
3-2: x 2 − y 2 = 7
3-1: z 2 − y 2 = 1 6
Hold on... the first and last equations look like a pythagorean triple I know. Let's bash those numbers in and see what we get. If z=5, x=4, and y=3, then
2-1: 5 2 − 4 2 = 9
3-2: 4 2 − 3 2 = 7
3-1: 5 2 − y 3 = 1 6
All these statements are true, so (x,y,z) = (4,3,5) is a solution, and therefore the solution is 3 × 4 × 5 = 6 0
(I am aware that this solution lacks the rigour I would like, but the solution jumped so clearly out at me, I could not help but see it)